PCSK9 inhibitors may improve cardiovascular outcomes—Can we afford them?. (1st October 2016) - Arbel, Ronen; Hammerman, Ariel; Triki, Noa; Greenberg, Dan
Abstract: Background/Objectives: Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) can significantly lower low-density lipoprotein (LDL) cholesterol levels. Early evidence suggests that use of PCSK9i also reduces the incidence of major adverse cardiovascular events (MACE). Our objective was to determine preliminary economic implications of PCSK9i use to avoid MACE, based on the current data from major phase III clinical trials. Methods: Outcome data of the 4529 patients treated with PCSK9i in the OSLER and ODYSSEY LONG TERM trials were collected from the published reports. Cost of preventing MACE was evaluated based on the existing outcome data and current US prices of PCSK9i. The pooled results were compared to the cost of curing Hepatitis C Virus (HCV) patients with novel HCV drugs. Results: PCSK9i treatment in the OSLER and ODYSSEY LONG TERM trials resulted in prevention of 35 MACE in a total of 4903 patient-years: 8 cardiovascular deaths, 22 myocardial infarctions, 0 strokes and 5 unstable anginas. The cost of PCSK9i drugs consumed during the trial's current follow-up period, could have reached 70, 172, 141. Therefore, the cost of preventing any MACE would be 2, 004, 918 and the cost of preventing one death would be 8, 777, 518. These figures are one hundred fold higher than the cost of curing one HCV patient ( 84, 000). Conclusions: According to the current published data, using PCSK9i to prevent MACE seems to be a very expensive strategy. If upcoming outcome trials will demonstrate similar results, it seems that at current prices, using these drugs would not be affordable for most healthcare systems. Highlights: Early evidence suggests that use of PCSK9i also reduces the incidence of major adverse cardiovascular events (MACE). The average estimate cost for one prevented MACE is over 2 M, and for one prevented death is almost 9 M. Clinicians should target PCSK9i therapy to the highest risk, most unmet need patients. Payers need to look for novel ways to significantly lower the cost of these drugs.